Digital Marketing Strategy on Online Purchase Decision on TikTok Online Shopping Platform - Handayani, Eliya Hikmah; Rasidi, Moh. (Golden Ratio of Social Science and Education, 2024)
This study aims to determine the factors that influence consumer purchasing decisions on TikTok shop and differences in TikTok shop compared to other e-commerce platforms. Using a descriptive qualitative approach, data were obtained through in-depth interviews, observation, and documentation of consumer actors in Sentul Village, Gading District, who use TikTok Shop as a shopping medium. The results show that creative content strategies, utilization of influencers, and the use of live streaming features significantly increase consumer buying interest, digital marketing has a significant effect, while influencers and online customer reviews have a positive effect on purchasing decisions.